366 A randomized double-blind placebo-controlled phase III study evaluating perioperative toripalimab combined with platinum-based doublet chemotherapy in resectable stage III NSCLC. (10th December 2020) - Wang, Wenxiang; Wu, Lin; Zhang, Wei; Lu, Shun; Fang, Haohui; Yu, Guohua; Zhou, Ming; Xing, Wenqun; Chen, Qixun; Li, Xingya; Yang, Nong; Ye, Minhua; et al.
Abstract : Background: Surgery remains the mainstay of treatment for resectable stage III non-small cell lung cancer (NSCLC). The preliminary results from some pilot trials have shown that neoadjuvant immunotherapy in NSCLC is safe and tolerable. 1 2 Hypothesizing that neoadjuvant toripalimab (a humanized anti-PD-1 antibody) plus chemotherapy can improve the outcome in resectable NSCLC, we are conducting a randomized, double-blind, placebo-controlled, phase III study to evaluate the efficacy and safety of toripalimab plus platinum-based doublet chemotherapy as neoadjuvant/adjuvant therapy for patients with resectable stage III NSCLC. Methods: This ongoing study enrolls patients aged 18–70 years with treatment-naïve, histopathologically confirmed resectable stage III NSCLC without EGFR mutation or ALK translocation, ECOG PS 0–1, and adequate organ function. Eligible subjects are randomized (1:1) into experimental or control group, to receive perioperative toripalimab 240 mg or placebo combined with chemotherapy for 4 cycle in total (Docetaxel 60–75 mg/m 2 or Paclitaxel 175 mg/m 2 with platinum [squamous histology] or Pemetrexed 500 mg/m 2 with platinum [non-squamous histology]) every 3 weeks for three cycles followed by surgery, and one more cycle after surgery, then monotherapy of toripalimab 240 mg or placebo every 3 weeks up to 13 cycles is delivered. Adjuvant radiotherapy is allowed. Randomization is stratified by tumor stage(IIIA vs IIIB), pathological type (squamous vs non-squamous), PD-L1 expression (PD-L1≥1% vs <1% or not evaluable) and planned surgical procedure (pneumonectomy vs lobectomy). Radiographic response is assessed within 4–6 weeks after last dose of neoadjuvant therapy, at 30 days after surgery and every 12 weeks thereafter. Primary endpoints are major pathologic response (MPR) rate evaluated by blind independent central pathology review (BIPR-MPR) and event-free survival evaluated by investigator (INV-EFS). Secondary endpoints include pathologic complete response (pCR) rate evaluated by BIPR and investigators (BIPR-pCR and INV-pCR), disease-free survival (DFS), 2–3 years OS rate, OS, safety, and feasibility of surgery. Exploratory endpoints are potential correlations between biomarkers and efficacy. A stratified Cochran Mantel Haenszel method will be used to assess binary endpoints. A Kaplan-Meier method, a stratified log-rank test and a stratified Cox proportional hazards model will be used to assess survival endpoints.Planned enrollment is 406 patients. The study is actively enrolling at 52 Chinese sites. Results: N/A Conclusions: N/A Acknowledgements: N/A Trial Registration: The Clinical trials. gov no NCT04158440 Ethics Approval: This study was approved by the Ethics Board of all the involved sites; Approval number of Shanghai Chest Hospital: LS1936 Consent: N/A References: Forde PM, Chaft JE, Smith KN, et al. Neoadjuvant PD-1 blockade in resectable lung cancer N Engl J Med 2018;378 :1976–1986 Hellmann MD, Chaft JE, William WN Jr, et al. Pathological response after neoadjuvant chemotherapy in resectable non-small-cell lung cancers: proposal for the use of major pathological response as a surrogate endpoint. Lancet oncol 2014;15:e42–50.